Regulation of Treg Cell Metabolism and Function in Non-Lymphoid Tissues - Yang, Kai (Frontiers in Immunology, 2022)
Regulator T cells (Tregs) play pivotal roles in maintaining immune tolerance and regulating immune responses against pathogens and tumors. Reprogramming of cellular metabolism has been determined as a crucial process that connects microenvironmental cues and signaling networks to influence homeostasis and function of tissue Tregs. In adaptation to a variety of non-lymphoid tissues, Tregs coordinate local immune signals and signaling networks to rewire cellular metabolic programs to sustain their suppressive function. Altered Treg metabolism in turn shapes Treg activation and function. In light of the advanced understanding of immunometabolism, manipulation of systemic metabolites has been emerging as an attractive strategy aiming to modulate metabolism and function of tissue Tregs and improve the treatment of immune-related diseases. In this review, we summarize key immune signals and metabolic programs involved in the regulation of tissue Tregs, review the mechanisms underlying the differentiation and function of Tregs in various non-lymphoid tissues, and discuss therapeutic intervention of metabolic modulators of tissue Tregs for the treatment of autoimmune diseases and cancer.